2016
DOI: 10.1186/s13104-016-1924-7
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of hypertension and cardiovascular disease risk factors among medical students at Makerere University College of Health Sciences, Kampala, Uganda

Abstract: BackgroundCardiovascular disease has become a leading global health challenge representing the largest cause of mortality in adults worldwide. Non communicable diseases are neglected in Uganda over infectious diseases. With increased urbanization, there is likely increase in burden of these NCDs yet there is paucity of reliable data regarding the NCD burden. We assessed the prevalence of hypertension and other cardiovascular disease risk factors among medical students at Makerere University, College of Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
7
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 24 publications
4
25
7
3
Order By: Relevance
“…The prevalence of hazardous alcohol drinking that was recorded in this study (26.7%) is lower than the 31.7%, 32.8%, 42.5%, 26%–45% and 51.9%, respectively, reported from university students in Uganda, Ethiopia, Cameroon, Tanzania and Kenya 25–29. Clearly, hazardous alcohol drinking is taking epidemic proportions among younger populations, which will have serious consequences on CVD occurrence, liver cirrhosis and other related health threats 3 8 30…”
Section: Discussioncontrasting
confidence: 58%
“…The prevalence of hazardous alcohol drinking that was recorded in this study (26.7%) is lower than the 31.7%, 32.8%, 42.5%, 26%–45% and 51.9%, respectively, reported from university students in Uganda, Ethiopia, Cameroon, Tanzania and Kenya 25–29. Clearly, hazardous alcohol drinking is taking epidemic proportions among younger populations, which will have serious consequences on CVD occurrence, liver cirrhosis and other related health threats 3 8 30…”
Section: Discussioncontrasting
confidence: 58%
“…Contrary to our findings, studies have observed that there was no association between elevated BMI and hypertension. 25,26 Though significant association was not found in our study with various risk factors. Other studies have shown high prevalence of cardiovascular risk factors among medical students.…”
Section: Discussioncontrasting
confidence: 62%
“…While no one was having hypertension in our study sample, 4% had pre-hypertension, which marks a risk of developing hypertension in future and this could be a result of unhealthy diet and stressful lifestyle as well as familial tendency. When compared to results from other studies done in the region and the world (8,19,20,21,22,23), this prevalence is not high. According to these studies, the prevalence of hypertension among medical students and other undergraduates with ages ranging from 18 to 36 years, varied between 1.3% and 17% while the prevalence of pre-hypertension was much higher.…”
Section: Discussionmentioning
confidence: 48%